Formation of Spiritual and Social Attitudes through Learning Akidah Akhlak in the Digital Era - Muhammad Abdullah Syauqi; Darmanto Darmanto; Rita Zunarti; Khairul Saleh; Bima Fandi Asy’arie; Olaniyi Jibril Ayuba (Mauriduna : Journal of Islamic Studies, 2025)
Studying the formation of students' spiritual and social attitudes through learning the Akidah Akhlak has always been a topic of discussion in education. Because these two attitudes are important assessment aspects in determining a student's promotion or graduation. The research aims to determine (1) the Implementation of assessing aspects of students' spiritual and social attitudes in learning moral beliefs, and (2) the obstacles in implementing assessments of students' spiritual and social attitudes. The focus of this research was conducted at MTs Negeri 1 East Lampung. This type of research is field research; the method used is a case study with a qualitative approach. The techniques in this research use interviews, observation, and documentation. There were 15 informants in this study. The findings of the discussion in the research include: First, implementation of assessing aspects of students' spiritual and social attitudes, namely, first, assessment planning, identifying core competencies (KI) and basic competencies (KD), formulating indicators, determining techniques, designing instruments, selecting instruments, and analyzing processes. Evaluation. During the implementation process, there are assessments, observations, self-assessments, peer-to-peer assessments, and journaling. Then, processing and reporting, determining scores, describing assessment achievements, recapitulation, reporting assessment results, and assessment follow-up. Second, the obstacle to forming students' spiritual and social attitudes is limited mastery of IT (Information Technology). Third, there are obstacles in selecting operational verbs that are appropriate to the material and time limitations available. Fourth, limited school financial budgets.